2016
DOI: 10.1080/19491034.2016.1150392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chromatin accessibility domains in human breast cancer stem cells

Abstract: Epithelial-to-mesenchymal transition (EMT) is physiological in embryogenesis and wound healing but also associated with the formation of cancer stem cells (CSCs). Many EMT signaling pathways are implicated in CSC formation, but the precise underlying mechanisms of CSC formation remain elusive. We have previously demonstrated that PKC is critical for EMT induction and CSC formation in inducible breast EMT/CSC models. Here, we used formaldehyde-assisted isolation of regulatory elements-sequencing (FAIRE-seq) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
2
19
2
Order By: Relevance
“…We have shown previously that the promotion of stem‐like phenotype in FoxQ1 overexpressing SUM159 cell line is associated with suppression of DACH1 and ZEB1 expression and upregulation of mRNA levels of MYC and TWIST2 10 and RNA‐seq results from the present study were consistent with these published observations (Figure S1C). At the same, some published changes in genes downstream of FoxQ1 7,9,14 were not validated in the RNA‐seq data from the present study, including PLD1, SNAI1, CTNNB1, JUP, S100A4, DCN, PDGFRB, CADM3, COL1A1, COL6A1, DSG2 , and TWIST1 (Figure S2A‐C). Two possibilities exist to explain the inconsistencies between published data and RNA‐seq results.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…We have shown previously that the promotion of stem‐like phenotype in FoxQ1 overexpressing SUM159 cell line is associated with suppression of DACH1 and ZEB1 expression and upregulation of mRNA levels of MYC and TWIST2 10 and RNA‐seq results from the present study were consistent with these published observations (Figure S1C). At the same, some published changes in genes downstream of FoxQ1 7,9,14 were not validated in the RNA‐seq data from the present study, including PLD1, SNAI1, CTNNB1, JUP, S100A4, DCN, PDGFRB, CADM3, COL1A1, COL6A1, DSG2 , and TWIST1 (Figure S2A‐C). Two possibilities exist to explain the inconsistencies between published data and RNA‐seq results.…”
Section: Resultscontrasting
confidence: 59%
“…Published studies have revealed multiple downstream targets of FoxQ1 in breast cancer 7‐10,14,15 . For example, Zhang et al 7 showed downregulation of CDH1 in highly metastatic breast cancer cell lines (eg, MDA‐MB‐435, MDA‐MB‐231, SUM149, etc) in comparison with breast cancer cell lines with low metastatic capacity (eg, MCF‐7, MDA‐MB‐361, BT20, etc) as well as upregulation of mesenchymal markers such as N‐cadherin (CDH2) and fibronectin 1 (FN1) and downregulation of CDH1 in FoxQ1 overexpressing HMLE cells when compared with EV cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7-9,11). A-D, RNA-seq analysis of genes not consistent with the published literatures (7,9,11). Results shown are mean ± S.D.…”
Section: Footnotesmentioning
confidence: 85%
“…Published studies have revealed multiple downstream targets of FoxQ1 in breast cancer (7)(8)(9)(10)(11)(12). For example, Zhang et al (7) showed downregulation of CDH1 (Ecadherin ) but upregulation of mesenchymal markers including CTNNA1 (catenin alpha 1), CDH2 (N-cadherin), and FN1 (fibronectin 1) in highly metastatic breast cancer cell lines (e.g., MDA-MB-435, MDA-MB-231, SUM149, etc.)…”
Section: Comparison Of Rna-seq Data With Published Literaturementioning
confidence: 99%